Supplier performance analysis using the Analytical Hierarchy Process (AHP) method - Agus Riyanto; Bayu Adytia Kurniawan; Gabriel Sianturi; Dina Oktafiani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This research aims to determine priorities in supplier selection. The determination of this supplier uses the Analytical Hierarchy Process (AHP) method by determining the criteria and sub-criteria of the supplier selection objectives. Each criterion and sub-criteria are arranged in a hierarchical structure and compared by determining the priority scale. The selection of suppliers is based on the largest global weight values. The selected supplier is PT. MMII with a global weight value of 0.280. The global weighted assessment has considered consistency in decision-making based on a consistency index, which must be below 10%. It shows that PT. MMII is selected based on existing criteria and sub-criteria compared to other suppliers. This study contributes to group decision-making involving experts to choose the most appropriate supplier.